Speech Act Analysis on Joe Biden's Speech about Covid-19 - Gita Yusanti; Ary Setya Budi Ningrum; Nurul Aini; Edwin Nuvianto Al Aziz (Masyarakat Linguistik Indonesia Universitas Andalas, 2022)
This study is to identify the utterances of particularized speech acts and illocutionary functions on Joe Biden's speech about Covid-19. The writer uses descriptive qualitative design to gain the research. The writer collects the data from the video content on YouTube named C-SPAN entitled President-elect Joe Biden COVID-19 Briefing and website named Rev formed as speech transcript. Joe Biden or Joseph Robinette Biden is the 46th president of the United States. From the analysis, the writer found three types of speech acts used by Joe Biden. The data used Searle's theory. They are the locutionary act, illocutionary act, and perlocutionary act. Then, the writer also found that illocutionary act is divided into five categories. They are assertive (42%), directive (18%), commisive (29%), expressive (9%), and declaration (2%). The most dominant type of illocutionary act is assertive or representative. Meanwhile, the most dominant type of illocutionary function used by him is promising function. From this study, it can be found the kinds of facial expressions, posture, and gestures of body language which are expressed by Joe Biden.